2007
DOI: 10.1152/ajpgi.00401.2006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for calcium signaling in hepatic stellate cells

Abstract: Progressive liver fibrosis (with the resultant cirrhosis) is the primary cause of chronic liver failure. Hepatic stellate cells (HSCs) are critically important mediators of liver fibrosis. In the healthy liver, HSCs are quiescent lipid-storing cells limited to the perisinusoidal endothelium. However, in the injured liver, HSCs undergo myofibroblastic transdifferentiation (activation), which is a critical step in the development of organ fibrosis. HSCs express P2Y receptors linking extracellular ATP to inositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…Early reports have shown secretion of prostaglandins F2 and D2 after stimulation with ATP (109). Recent studies revealed that P2Y receptors link extracellular ATP to inositol triphosphate-mediated cytosolic calcium signals resulting in localized calcium signaling and cell contraction (110,111).…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…Early reports have shown secretion of prostaglandins F2 and D2 after stimulation with ATP (109). Recent studies revealed that P2Y receptors link extracellular ATP to inositol triphosphate-mediated cytosolic calcium signals resulting in localized calcium signaling and cell contraction (110,111).…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…Resting HSCs usually locate in the perisinusoidal space with vitamin A-containing lipid droplets. However, their morphology and physiology alter dramatically during myofibroblastic transdifferentiation, also known as activation, which serves as the critical step in the initiation as well as progression of liver fibrosis [2,3]. The most important phenotypic alterations of activated HSCs, as defined by theirs actions in liver fibrogenesis, lie in the active proliferation, autocrine and/or paracrine fibrogenetic factors, inordinate ECM synthesis and secretion, and resistance to apoptosis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Following liver injury of any etiology, HSCs undergo a response known as ''activation,'' which is the transition of quiescent cells into proliferative, fibrogenic, and contractile myofibroblasts [2]. Several studies recently reported that the number of HSCs are increased associated with its biological properties of HSCs proliferation and counteration of apoptosis, when stimulated by fibrogenic stimuli [3][4][5].…”
Section: Introductionmentioning
confidence: 99%